2006
DOI: 10.1074/jbc.m513375200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heme Iron Coordination and Protein Structure in the Dynamics and Geminate Rebinding of Nitric Oxide to the H93G Myoglobin Mutant

Abstract: The influence of the heme iron coordination on nitric oxide binding dynamics was investigated for the myoglobin mutant H93G (H93G-Mb) by picosecond absorption and resonance Raman timeresolved spectroscopies. In the H93G-Mb, the glycine replacing the proximal histidine does not interact with the heme iron so that exogenous substituents like imidazole may coordinate to the iron at the proximal position. Nitrosylation of H93G-Mb leads to either 6-or 5-coordinate species depending on the imidazole concentration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 56 publications
4
34
2
Order By: Relevance
“…Remarkably, the rebinding of NO to the heme alone in solution is also mono-exponential (7.5 ps) but with a constant base line (8%) that corresponds to NO escape into the solvent (46,47). Thus, a time constant of ϳ7 ps for NO rebinding to the 4-coordinate heme after dissociation (either thermal or photoinduced) seems to be the lower limit for this barrierless process when no protein structure is involved, in agreement with calculations (16,48) and with temperature-dependent rebinding measurements (42).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Remarkably, the rebinding of NO to the heme alone in solution is also mono-exponential (7.5 ps) but with a constant base line (8%) that corresponds to NO escape into the solvent (46,47). Thus, a time constant of ϳ7 ps for NO rebinding to the 4-coordinate heme after dissociation (either thermal or photoinduced) seems to be the lower limit for this barrierless process when no protein structure is involved, in agreement with calculations (16,48) and with temperature-dependent rebinding measurements (42).…”
Section: Discussionsupporting
confidence: 69%
“…It is noteworthy that, despite the efficient and fast geminate recombination, the k off value for 5c-NO AXCP (4.1 ϫ 10 Ϫ4 s Ϫ1 ) is of the same order of magnitude as 5c-NO heme protein complexes such as sGC ( (16). The high geminate recombination efficiency imposed by the proximal heme environment of AXCP implies that the typical k off value is due to an elevated value of k 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Met80 rebinding involves at least two electronic states: 1,4,11,20 the ground state singlet (s), associated with the bonded state, and the quintet (q), associated with the unbonded state. In this work, the classical CHARMM force field in the heme pocket has been extended by incorporating ab initio PES calculations.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Therefore, the amine nitrogen and heme iron cannot keep the optimal distance and the angle (C-N-Fe) to form an MI complex. A previous study reported that the potential energy of coordinate binding between the heme iron of myoglobin and nitric oxide depends on the distance (Negrerie et al, 2006). The potential energy reached the maximum at a distance of approximately 1.8 Å and then decreased dramatically according to dissociation between the heme iron and nitric oxide.…”
Section: Discussionmentioning
confidence: 99%